Peran Pola Komunikasi Antar Budaya Dalam Masyarakat Terhadap Hubungan Inklusif Antar Kelompok Agama - Kusuma, Adhi; Saputra, , Ilham; Al Mifta, Ardian Fikri; Rahmawati, Rahmawati; Hidayatullah, Ariq (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The communication process is a fundamental thing in social life, communication is a very important process because by indirect communication we can understand, attitudes, behaviors and actions from the social environment. This research aims to describe barriers in communication between cultures and religions, and also describe inclusive relationships between religious communities. In this study, a literature study research method is used by presenting research results from scientific papers. In this study, preventive measures in conflicts between religious communities are to reduce egocentrism and also mutual respect between religious people.